Study on the electric resistance method in crack depth measurements - Gu, Jiahui; Chen, Liang; Wan, Yu; Teng, Yaozong; Yan, Shufa; Hu, Liang; Wang, Jiahao; Luo, Hanxuan (Frontiers in Earth Science, 2023)
Obtaining geometric parameters, especially depth, and describing the morphological characteristics of cracks are of great significance to control engineering disasters and accidents caused by cracks. The electric resistance method is based on the principle of differences in electrical properties between cracks and soil, which could be used to measure the single crack depth at project sites. There exists an Rmin value corresponding to a specific electrode distance d value at each Rf-d value obtained by laboratory experiments. Furthermore, a two-dimensional finite element model of soil with a single crack is established to carry out numerical simulation analysis considering the crack width W, crack depth D and complex crack conditions. The results reveal dynamic variation rules of soil resistance after crack development, and for each Rf-d value, the electrode distance d value corresponding to the Rmin value is approximately equal to the crack depth D. In the range of the electric field, the offset and rotation of the crack have little effect, while the measurement results have a strong dependence on relocation movement. The regulation gives guidance to the inversion analysis of crack depth D at project sites and has been applied in crack depth measurements of an expansive soil slope. The electric resistance method as a proposed integrated approach is of great significance and brings new perspectives into the study of crack depth measurements for field applications.